Structure-induced spreading of liquid in micropillar arrays - Priest, C.; Forsberg, P.; Sedev, Rossen; Ralston, J. (2012)
Contact angle measurements on micropillar arrays were used to determine the conditions that trigger spontaneous penetration of liquids into surface structures. Square micropillars (20 µm) were fabricated in photoresist or quartz and modified chemically to alter the inherent contact angle (i.e., for a flat surface). The lattice spacing of the pillar array and pillar height was also adjusted to investigate the influence of geometry on the wetting behavior. A critical inherent contact angle, 9 0 , was observed below 90°, at which enhanced hydrophobicity switches to enhanced hydrophilicity. This differs from Wenzel's prediction of ? 0 = 90°. The transition is not a Cassie-Wenzel state transition. Above the critical angle, the static advancing contact angle increased with pillar coverage due to pinning. Below the critical angle, liquid spreads ahead of the droplet between the pillars to form a stable film. An example of chemical detection and the implications for multiphase microfluidics is discussed. © Springer-Verlag 2011.